1996
DOI: 10.1016/0304-3959(95)00095-x
|View full text |Cite
|
Sign up to set email alerts
|

The NMDA receptor antagonist MK-801 reduces Fos-like immunoreactivity in central trigeminal neurons and blocks select endocrine and autonomic responses to corneal stimulation in the rat

Abstract: The N-methyl-D-aspartate (NMDA) receptor is implicated in multiple aspects of pain processing by the central nervous system. However, the role of NMDA receptors in the endocrine and autonomic aspects of nociception remains uncertain. The present study examined the influence of the NMDA receptor antagonist, MK-801 (0.02-2.0 mg/kg, intracarotid), on the adrenal and autonomic responses to corneal stimulation (mustard oil, 20% sol.) in barbiturate-anesthetized rats. Fos-like immunoreactivity (Fos-LI) evoked by cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
27
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 44 publications
4
27
0
Order By: Relevance
“…Further, lesions of the RVM or Vi/Vc transition zone either eliminated or significantly attenuated mechanical hyperalgesia/allodynia after masseter inflammation. These findings extend previous observations on the role of the Vi/Vc transition zone in trigeminal processing of persistent noxious input (Bereiter et al, 1994(Bereiter et al, , 1996Ikeda et al, 2003). The results suggest that the Vi/Vc-RVM pathways are activated after inflammation and play a critical role in facilitating orofacial hyperalgesia.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Further, lesions of the RVM or Vi/Vc transition zone either eliminated or significantly attenuated mechanical hyperalgesia/allodynia after masseter inflammation. These findings extend previous observations on the role of the Vi/Vc transition zone in trigeminal processing of persistent noxious input (Bereiter et al, 1994(Bereiter et al, , 1996Ikeda et al, 2003). The results suggest that the Vi/Vc-RVM pathways are activated after inflammation and play a critical role in facilitating orofacial hyperalgesia.…”
Section: Discussionsupporting
confidence: 83%
“…We have shown recently that activated neurons in the Vi/Vc transition zone projected to the rostral sites such as the nucleus submedius of the thalamus, parabrachial nucleus, and lateral hypothalamus (Ikeda et al, 2003), structures known to participate in pain transmission and modulation. Studies suggest that Vi/Vc neurons are involved in multifacets of pain processing such as autonomic and somatovisceral functions related to persistent pain responses (Bereiter et al, 1994(Bereiter et al, , 1996Imbe et al, 1999).…”
Section: Indexing Terms: Fluorogold; Freund's Adjuvant; Fos; Descendimentioning
confidence: 99%
“…The parabrachial nucleus is involved in processing trigeminal nociceptive input and integrating emotional and autonomic responses (see Feil and Herbert 1995). The major projections from Vi/Vc are to the Sm and parabrachial nucleus, supporting the conclusion that this region plays a role in autonomic and hormonal functions and is emotionality related to persistent pain (Bereiter et al ., 1996; Ikeda et al ., 2003) (Fig. 3).…”
Section: Functional Input and Output Of The Vi/vc Transition Zonesupporting
confidence: 66%
“…The pathways from the caudal portions of the spinal trigeminal nucleus to brainstem or spinal cord regions that control the adrenal and autonomic responses to corneal stimulation have not been determined with certainty. However, topical application of mustard oil to the corneal surface induced Fos-immunoreactivity in neurons in the 5i-5c and in the NTS (Bereiter et al, 1996). In addition, it has been reported that nociceptive primary afferents fibers terminate in the rostral STC as well as in the caudal 5i and 5c (Westrum et al, 1981;Marfurt and Turney, 1984;Shigenaga et al, 1986a-c).…”
Section: Projections From the Stc To The Ntsmentioning
confidence: 93%